The United States and the Challenges of the Hashemite Kingdom of Jordan’s Internal Stability: A Historical Retrospective - L. R. Khlebnikova (Вестник Московского Университета. Серия XXV: Международные отношения и мировая политика)
The Hashemite Kingdom of Jordan has been playing an important role in the Middle Eastern subsystem being heavily affected by the events in the Israeli-Palestinian conflict zone, as well as wars in Iraq or Syria. External factors compound the Jordanian authorities’ efforts to overcome the numerous internal economic, social and political challenges causing regular protests, sometimes of a quite considerable scale. At the same time Jordan is extremely dependent on external support. It has been receiving the bulk of aid from the United States that regards stability of Jordan as one of key interests in the region and often acted as a mediator between the State of Israel and the Hashemite Kingdom. This paper provides a detailed examination of the rationale behind the US aid to Jordan and the fluctuations in its volume and structure at different phases of the US-Jordanian relations with a focus on the period between two waves of protests — of 1989 and 2011. Special attention is paid to the ‘Israeli factor’ which would play a crucial role in the US-Jordanian relations. The paper’s first section contains a brief overview of the history of the relations between the United States and the Hashemite Kingdom of Jordan during the Cold War. The second section focuses on the last decade of King Hussein’s rule (1989–1999). The final section examines the policies of his son, Abdullah II — from his ascension to throne until the ‘Jordanian Spring’ of 2011. The conclusion is drawn that the United States was always aware of fragility of Jordanian statehood built around the king. However, the importance of Jordan for addressing pivotal regional сhallenges (such as countering the spread of Nasser’s Egypt and the Soviet Union’s influence in the region, the Arab-Israeli conflict and — later — the Israel-Palestinian peace process or the War on Terror), forced the consecutive US administrations, regardless of their party affiliation, to turn a blind eye to the lack of real progress in the implementation of liberal reforms in the Hashemite Kingdom. Moreover, it was the steady flow of foreign assistance that allowed the Jordanian monarchy to halt promised reforms. Thus, it seems quite natural that the Arab Awakening of 2011 did affect Jordan creating the most serious political challenge to the royal family’s rule since the late 1980s.